Penentuan Blacksite dengan Metode Z-Score pada Koridor Ruas Jalan Alianyang – Jalan Pangeran Natakusuma – Jalan Danau Sentarum Kota Pontianak - Heri Azwansyah; Umar (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Population growth is creating a high demand for transport, which is causing problems for transport facilities and infrastructure. The Jalan Alianyang - Jalan Pangeran Natakusuma - Jalan Danau Sentarum corridor in Pontianak City has a moderately high accident frequency with a total of 40 accidents involving motorcycles, cars, loaded trucks and pedestrians. The main objective of this research is to determine the accident prone areas using the Z-score method in the corridor of Jalan Alianyang-Jalan Pangeran Natakusuma-Jalan Danau Sentarum, Kota Pontianak. The data was obtained from the Pontianak Municipal Police as traffic accident data from 2018 to 2023. The data was analysed based on accident characteristics, and accident prone areas (blacksite s) were determined using the Z-score method. Primary data was obtained from the results of field surveys on all segments of the study road corridor. Based on the analysis of the blacksite identification using the z-score method, the location of the z-score data of the accident prone area (blacksite ) and its vulnerability class is obtained, namely segment 3 with z-value = 0.413 (very low accident prone), segment 4 with z-value = 0.531 (very low accident prone) and segment 5 with z-data = 1.097 (very high accident prone). The characteristics of the traffic accidents are dominated by victims with minor injuries with a total of 52 persons, the incidents often occurred on Saturdays with a total of 8 incidents and occurred between 12:00 and 17:59 adding up to 18 events, the most serious accident occurred in segment 5 with a total of 11 events, the accidents are dominated by the male gender with a total of 29 persons and the dominant type of collision that occurs is the frontal type with a total of nine events.